Resident Peer Review Process: An Innovative Teaching Model in an Internal Medicine Residency Program - Malayala, Srikrishna V (Cureus, 2021)
Introduction Medical peer review is an integral part of the performance improvement process in any hospital. The very first exposure to the peer review process in a physician’s career is typically after graduation and when they start practicing as an attending physician. We implemented a “Resident Peer Review Process” training module in our Internal Medicine residency program with an intention to familiarize the residents about peer review. Methods The resident peer review process was implemented over a period of four weeks with the “resident peer review committee” having representation from all three Postgraduate Year (PGY) levels. The committee reviews the cases referred to them over a period of four weeks through a process of weekly meetings and adjudicates the cases. If any deficiency is identified, the committee will provide feedback to the residents involved in the case and presents the educational points identified from the adjudication at the end of the module as a morning report. Results Eighty-nine (89) cases were reviewed through this process over a span of two years. About 77.5% of the cases were identified to have a deficiency. Teaching points were identified and presented in Week 4 meetings in 80.9% of the cases that had a deficiency. The residents provided a positive response and said that the process improved their quality of patient care (98%), professionalism (95%), systems-based practice, practice-based learning (90%), medical knowledge (88%), and interpersonal and communications skills (87%).  Discussion This resident-driven, novel, and innovative model can be a successful teaching methodology for Internal Medicine residents to augment Patient Safety and Quality Improvement and could be implemented in residency programs irrespective of the size and specialty.